Effects of Formulation and Baking Process on Acrylamide Formation in Kolompeh, a Traditional Cookie in Iran - Fatemeh Shakeri; Somayeh Shakeri; Sajad Ghasemi; Antonio Dario Troise; Alberto Fiore (Journal of Chemistry)
Thermal treatments and recipes are two critical aspects for the formation of acrylamide at ordinary household cooking conditions and industrial level. Kolompeh is a traditional Iranian cookie, and the aim of this study was to monitor acrylamide formation in four different recipes: traditional sugary Kolompeh (TSK), traditional simple Kolompeh (TSIK), industrial sugary Kolompeh (ISK), and industrial simple Kolompeh (ISIK). Along with the measurement of reducing sugars, moisture, and pH, acrylamide was quantified by gas chromatography mass spectrometry (GC-MS). Results indicated that acrylamide content was 1758, 1048, 888, and 560 μg/kg for TSK, TSIK, ISK, and ISIK, respectively, revealing that the kind of thermal treatment in combination with higher concentrations of reducing sugars were the major driver for acrylamide formation. In particular, acrylamide concentration in TSIK direct heating was 1.87 times higher than industrial indirect heating treatment, highlighting that domestic preparation of Kolompeh required a specific attention as a source of potential toxic molecule formation.